Creating future young entrepreneur in the new normal: the role of facilitative law, normative support, and entrepreneurial knowledge / Nurul Hidayana Mohd Noor, Mahazril 'Aini Yaacob and Noralina Omar - Mohd Noor, Nurul Hidayana; Yaacob, Mahazril 'Aini; Omar, Noralina (2021)
Fostering entrepreneurship in the country has been the main national agenda since entrepreneurship helps to increase economic growth, reduce unemployment, and support modernization. In Malaysia, there is almost 14 million youth population in 2021 and they are the sources of future entrepreneurs. Promoting entrepreneurship among youths is critical in achieving the goal of the Malaysian government in becoming an entrepreneurial country by 2030. Hence, understanding youth perception about contextual factors that support entrepreneurship intention can be a contribution to the advancement of more active approaches and systems to support the goals. The theory of planned behaviour (TPB) is the predominant theory that examines the impact of contextual factors on entrepreneurship intention. Based on TPB, the purpose of this study is to examine the influence of facilitative law, normative support, and entrepreneurial knowledge on the entrepreneurship intention of the younger generation. In the study, a model was recommended and empirically examined on a sample of 248 Malaysian youths. The results of the survey showed that all factors affect the entrepreneurship intention of youths and entrepreneurial knowledge emerged as the main significant predictor. The paper contributes to the literature by empirically testing how some factors such as individual, community, and country-level factors may affect the entrepreneurship intention during the new normal era. The outcomes of the study may have valuable connotations for policymakers, practitioners, and future researchers.